ROLE AND FUNCTIONS OF THE COURT ADVISERS OF THE COURT FOR CHILDREN IN MALAYSIA: LESSONS LEARNT FROM SELECTED JURISDICTIONS - Md Eusofe, Nur Ezaitie Nabihah; Mohd Yusoff, Jal Zabdi; Thambapillay, Sridevi (The Malaysian Journal of Social Administration, 2023)
Court advisers form an important component in the setup of the Court For Children in Malaysia. They are appointed to assist the magistrate in matters relating to children who are brought before the court. These children include children in need of care and protection, children in need of protection and rehabilitation, children beyond control, children who are trafficked and abducted, and children in conflict with the law. However, this article will only focus on children in conflict with the law. Section 11(2) of the Child Act 2001 provides that the court advisers are responsible to advise the magistrate on the order to be made once the child is found guilty. Not only that, they may also advise the parents or guardian of the child to the extent that they may be considered as the protector of “the welfare component” of the legal process in dealing with a child that has been brought before the Court For Children. However, their functions are not clearly explained as the relevant provision in the Child Act 2001 is too general. Therefore, this article intends to explore the role and functions of the court advisers in Malaysia by analysing the position in Singapore and India. These two countries are amongst the British commonwealth countries in Asia that have roles similar to court advisers in their Juvenile Justice System. Hence, this article will compare and contrast the role and functions of the court advisers in Malaysia with these two jurisdictions in order to identify the best practices. This would in turn enhance the role of the court advisers in Malaysia and in the long run, safeguard the welfare of the children produced before the Court For Children. Keywords: children, conflict with law, court advisers, functions, comparative